2023
DOI: 10.21037/atm-22-6423
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge mapping of research on the mitochondrial unfolded protein response: a bibliometric and visual analysis

Abstract: Background The mitochondrial unfolded protein response (UPR mt ) is a mitochondria stress response, which exerts a crucial role in maintaining mitochondrial proteostasis during stress. However, there is no bibliometric analyses systematically studied this field which could comprehensively review research trends, evaluate publication performances and provide future perspectives. Methods Articles investigating UPR mt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Figure 3B depicts a collaboration network of countries/regions with at least five publications, where the size of each node represents the number of publications, and the thickness of the lines indicates the strength of cooperation. 20 , 21 The color of each node reflects the average publication date, with yellow indicating a later publication date. 22 It can be observed that South Korea, the United States, Japan, and Germany made significant contributions in the early stage of research with earlier publication dates, while China, Brazil, Switzerland, Thailand, and Colombia gradually entered the research field in recent years and have been making remarkable progress, particularly in the case of China, which has taken a central position in the field in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3B depicts a collaboration network of countries/regions with at least five publications, where the size of each node represents the number of publications, and the thickness of the lines indicates the strength of cooperation. 20 , 21 The color of each node reflects the average publication date, with yellow indicating a later publication date. 22 It can be observed that South Korea, the United States, Japan, and Germany made significant contributions in the early stage of research with earlier publication dates, while China, Brazil, Switzerland, Thailand, and Colombia gradually entered the research field in recent years and have been making remarkable progress, particularly in the case of China, which has taken a central position in the field in recent years.…”
Section: Resultsmentioning
confidence: 99%
“…The warmer colors of the nodes signify later average publication times. [15][16][17][18] It appears that the United States made outstanding contributions in the early research of this field with earlier average publication times, while China has recently published a large number of academic achievements. Additionally, Table 1 lists relevant information of the top 10 countries/regions in terms of publication volume, with the United States (484, 34.35%), China (272, 19.30%), and Germany (174, 12.35%) accounting for 66% of the total publications.…”
Section: Analysis Of Countries/regionsmentioning
confidence: 99%
“…In bibliometrics, network charts are frequently used to report the collaborations and cooccurrences involving the most active international entities across countries, research institutes, departments, authors, and keywords. [3,28,[46][47][48][49][50] However, these charts often suffer from unclear labeling and relationships between members. To address these limitations, this study will demonstrate the use of 5 CNCs in AI for critical care.…”
Section: Five Cncs Shown For Coauthorship Networkmentioning
confidence: 99%
“…The figure illustrates 3 types of network charts used in bibliometric analyses: clusters [3,28,[46][47][48][49][50]52] (clusters are randomly scattered); circles [53][54][55][56][57][58] (members are grouped by cluster and bubble size), and chords [43][44][45]59] (similar to the circle chart with significant relationships between members). Readers will find that the CNC with a dashboard-type representation has a meaningful and clear interface.…”
Section: Comparison Of 3 Network Chartsmentioning
confidence: 99%